Upaya Meningkatkan Motivasi Belajar dengan Menerapkan Model Reading Guide Berbasis PAIKEM bagi Peserta Didik di SDN Model Mataram - Suryaningsih, Evy (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2016)
This study aimed to know the effectiveness of implementing Guide Reading Model Approach based PAIKEM in effort to improve students learning activities at class II.A of SD Negeri Model Mataram. Significant of this study was it could be analyzed and invention sources in implementing learning process at real class. For teachers it could improve competence in learning process and for students could improve learning motivation which has effect in improving students learning achievement. This research conducted in two cycles, activities in every cycle were planning, acting, observing, reflecting. The result in cycle II showed that result of teachers’ observation got mean score (4,64) and students’ observation got mean score (4,32). Then result of improving students’ learning activities improved with mean score was (81,00), means indicator of completeness (> 70,00) was reached. Because indicator of completeness had been proved success so this study was stopped in cycle II.